2009
DOI: 10.1007/s10681-009-9976-6
|View full text |Cite
|
Sign up to set email alerts
|

Partial resistance to black spot disease in diploid and tetraploid roses: general combining ability and implications for breeding and selection

Abstract: Black spot disease, incited by the fungus Diplocarpon rosae Wolf, is the most important disease of roses (Rosa hybrida L.) in the outdoor landscape. Though partial resistance exists in cultivated germplasm, the genetic basis of this trait has not yet been elucidated. Six diploid and six tetraploid rose cultivars were crossed in two factorial combining ability arrays. Whole plant and detached leaf inoculation methods were used to assess partial resistance under two different disease pressures using a characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 16 publications
2
15
1
Order By: Relevance
“…Sporulation capacity has been previously documented as a component of partial resistance in rose (Xue & Davidson, 1998). A previous inoculation experiment with D. rosae race 3 (isolate GVH) showed that the same detached leaf assay technique used in the present study could serve as a proxy for whole plant inoculations when assessing partial resistance (Whitaker & Hokanson, 2009). In that study, some susceptible genotypes with high partial resistance produced small and/or few spore masses under high disease pressure but did not exhibit sporulation under low disease pressure.…”
Section: Discussionmentioning
confidence: 94%
“…Sporulation capacity has been previously documented as a component of partial resistance in rose (Xue & Davidson, 1998). A previous inoculation experiment with D. rosae race 3 (isolate GVH) showed that the same detached leaf assay technique used in the present study could serve as a proxy for whole plant inoculations when assessing partial resistance (Whitaker & Hokanson, 2009). In that study, some susceptible genotypes with high partial resistance produced small and/or few spore masses under high disease pressure but did not exhibit sporulation under low disease pressure.…”
Section: Discussionmentioning
confidence: 94%
“…Conidial concentrations of the inoculum varied with availability on each date and ranged between 30,000 and 100,000 conidia/ mL. These concentrations were within the range of inoculum concentrations used in other studies (Whitaker et al, 2007b(Whitaker et al, , 2010bWhitaker and Hokanson, 2009a). At each of the five inoculation dates one susceptible control cultivar was used.…”
Section: Methodsmentioning
confidence: 78%
“…Such race-specific resistance can only be characterized with controlled inoculations of roses with individual races as opposed to a field setting where the presence and prevalence of specific races are not known. Using characterized races for inoculations under controlled conditions is also advantageous when surveying for partial resistance (Whitaker and Hokanson, 2009a;Xue and Davidson, 1998).…”
mentioning
confidence: 99%
See 2 more Smart Citations